UPAYA MENINGKATKAN KETERAMPILAN BERBICARA SISWA DI DEPAN KELAS DENGAN TEKNIK PROBLEM SOLVING MELALUI BIMBINGAN KELOMPOK KELAS X SMA ADHYAKSA JAMBI - Auria Khairina; Rasimin Rasimin; Dinny Rahmayanty (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
Based on the results of interviews with guidance and counseling teachers at SMA ADHYAKSA 1 Jambi, researchers found that the problem at this school was the low speaking skills of students, where students did not have the confidence and courage to speak when making presentations in front of the class they did not master the material. during the learning process. The research aimed to improve students' speaking skills in front of the class using problem-solving techniques through group tutoring services at SMA ADHYAKSA 1 Jambi. The research method used is that the researcher uses service action research. This research is planned to be carried out in three cycles, and in one cycle there are two meetings. When carrying out service actions, researchers prepare cameras, questionnaires, observation sheets, and service implementation plans. When providing action services using problem-solving techniques through group guidance services, students go through four stages, namely planning, implementation, evaluation and reflection. At the action stage the researcher explains the material and then conducts questions and answers where the questions are about solving a problem then students allowed to speak to answer the questions given so that problem solving techniques are applied in group guidance.